The effect of covid-19 pandemic on retirement planning. Evidence from private employed persons - Fan, Yong En; Foo, Qin Yu; Hoh, Suet Ne; Khor, Yin Ping (2022)
Retirement planning is essential practice to protect post-retirement well-being. This study aimed to identify the effect of Covid-19 pandemic on retirement planning. There are income, financial literacy, savings behaviour and goal clarity are implied for this study to identify their relationship between retirement planning as impacted by the pandemic. Private employed persons are mostly affected among the working population and had became the target of this study. Total of 393 survey had been collected from regions including Selangor, Wilayah Persekutuan (Kuala Lumpur and Putrajaya), Perak, Johor and Penang. Afterwards, Statistical Package for Social Science (SPSS) applied for data analysis. There are few test conducted including reliability test, consistency test and significance of model test. Income, financial literacy, savings behaviour and goal clarity are shown to be significant variables leading to retirement planning as impacted by Covid-19 pandemic. Implications are suggested to all related authorities to educate people in doing better retirement planning.